A global soil moisture product at 1 km resolution based on Sentinel-1 (2016-2022) - Dong Fan; Tianjie Zhao; Xiaoguang Jiang; Almudena García-García; Toni Schmidt; Luis Samaniego; Sabine Attinger; Hua Wu; Yazhen Jiang; Jiancheng Shi; Lei Fan; Bohui Tang; et al. (PANGAEA, 2025)
Soil moisture, although a small fraction of total water content, plays a critical role in the Earth extquotesingles surface water-heat cycle by influencing processes such as evaporation, infiltration, and vegetation growth and development. Remote sensing has emerged as a critical method for obtaining global-scale soil moisture data. A dual-polarization algorithm (DPA) is proposed and the dual-polarization (VV+VH) observations from the Sentinel-1 C-band synthetic aperture radar are used to generate a global soil moisture dataset with a spatial resolution of 1 km. Due to the observation mode of Sentinel-1, the temporal resolution of this dataset is higher in European and high latitude regions compared to other continents and lower latitude regions. The dataset is provided in raster format, with one set of ascending and one set of descending data for each day, and to ensure data quality, certain areas not suitable for soil moisture retrieval have been excluded, such as water bodies, permanent wetlands, frozen areas, ice and snow covered surfaces, and urban and built-up areas. Feedback and collaboration to improve the dataset is encouraged.